Radio, modern communication media and the technological sublime. - Craig, Douglas B. (Radio Journal: International Studies in Broadcast & Audio Media, 2008)
Leo Marx and others have argued that the reception of technology in the United States during the nineteenth century was conditioned by the 'technological sublime'. John F. Kasson defined this as a 'powerful emotion, utility, and moral purpose', suffused with the conviction that the health of the republic was indicated and improved by technological progress. This article provides different perspectives on the American technological sublime, as well as an exploration of its transference to radio and then television. Although there was no shortage of enthusiasm for radio, and for its potential to reconfigure the republic, its reception was not as uncomplicated as the idea of the technological sublime suggests. Interwar hopes for broadcasting and its potential social effects spoke as much to American insecurities as to their dreams; deep fears about social cohesion, cosmopolitanism and pluralism underpinned promises of a new age of radio culture and citizenship. Most Americans did not need to be persuaded of the benefits of radio and later media technologies, but those who identified with the cultural and political establishments needed to be reassured that their position and values would not be threatened by it.